Bioethics and the Rule of Law: A Classical Liberal Theory. Issue 3 (21st May 2020) - Brodrick, Michael
Abstract: Heated debates over healthcare policy in the United States point to the need for a legal framework that can sustain both moral diversity and peaceful cooperation. It is argued that the classical liberal Rule of Law, with its foundation in the ethical principle of permission, is such a framework. The paper shows to what extent the current healthcare policy landscape in the United States diverges from the rule of law and suggests how the current framework could be modified in order to better approximate that ideal. Two objections are then answered. The first is that the rule of law cannot be realized due to the structure of legislatures. The second objection is that government should guarantee both liberty and all of the necessary conditions of autonomy.